Metabolism of 2,4-Dichlorophenoxyacetic Acid (2,4-D) in Soybean Root Callus : EVIDENCE FOR THE CONVERSION OF 2,4-D AMINO ACID CONJUGATES TO FREE 2,4-D - Davidonis, Gayle H. (1980)
An auxin-requiring soybean root callus metabolized [1-(14)C]-2,4-dichlorophenoxyacetic acid (2,4-D) to diethyl ether-soluble amino acid conjugates and water-soluble metabolites. The uptake in tissue varied with incubation time, concentration, and amount of tissue. Uptake was essentially complete (80%) after a 24-hour incubation and the percentage of free 2,4-D in the tissue fell to its lowest point at this time. At later times, the percentage of free 2,4-D increased and the percentage of amino acid conjugates decreased, whereas the percentage of water-soluble metabolites increased only slightly. Similar trends were seen if the tissue was incubated for 24 hours in radioactive 2,4-D, followed by incubation in media without 2,4-D for 24 hours. Inclusion of nonlabeled 2,4-D during the 24-hour chase period did not reduce amino acid conjugate disappearance but did reduce the percentage of free [1-(14)C]2,4-D. Thus, an external supply of 2,4-D does not directly prevent amino acid conjugate metabolism in this tissue. It is concluded that 2,4-D amino acid conjugates were actively metabolized by this tissue to free 2,4-D and water-soluble metabolites.